2020
DOI: 10.1055/s-0040-1713746
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy without Radiation in Colorectal Cancer

Abstract: In colon cancer, primary surgery followed by postoperative chemotherapy represents the standard of care. In rectal cancer, the standard of care is preoperative radiotherapy or chemoradiation, which significantly reduces local recurrence but has no impact on subsequent metastatic disease or overall survival. The administration of neoadjuvant chemotherapy (NACT) before surgery can increase the chance of a curative resection and improves long-term outcomes in patients with liver metastases. Hence, NACT is being e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 92 publications
0
4
0
1
Order By: Relevance
“…Third, we evaluated the effect of preoperative CRT with S-1. Tumor shrinkage due to preoperative treatment may allow improved curative surgery [ 33 , 34 ], and this could also be expected to be associated with improved anal function preservation [ 35 , 36 ]. Among patients with Rb and Rb-P lesions, 56% were able to achieve anal preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we evaluated the effect of preoperative CRT with S-1. Tumor shrinkage due to preoperative treatment may allow improved curative surgery [ 33 , 34 ], and this could also be expected to be associated with improved anal function preservation [ 35 , 36 ]. Among patients with Rb and Rb-P lesions, 56% were able to achieve anal preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy itself can produce significant local responses at sites of bulky primary disease, including achieving complete pathologic regression in rectal cancer without radiation. 38 These local effects of full-dose Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Another important finding from PRODIGE 23 and RAPIDO was the impressive pathologic CR rates in the TNT groups—28% in both studies. Chemotherapy itself can produce significant local responses at sites of bulky primary disease, including achieving complete pathologic regression in rectal cancer without radiation 38. These local effects of full-dose chemotherapy are well established in a variety of tumors and can influence local tumor outcomes, beyond their role in treating micrometastatic disease 39,40.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we evaluated the effect of preoperative CRT with S-1. Tumor shrinkage due to preoperative treatment may contribute to improved curative surgery [28,29], and it can also be expected to be associated with improved anal function preservation [30,31]. Similar studies using S-1 have reported pCR rates of 22.2% [27] and 10.8% [21], although there were slight differences in the regimen.…”
Section: Discussionmentioning
confidence: 99%